Strongyloidiasis – A rare cause for recurrent urinary tract infection in a cirrhotic - Kunnathuparambil, Sojan George; Potti, Sanakara Narayanan; Antony, Thekkanath Paul; Venugopal, Reshma (Indian Journal of Case Reports, 2020)
Strongyloides stercoralis is an intestinal nematode that is commonly found in the tropical regions. Strongyloid larvae are very rarely seen in urine, especially in non-renal transplant patients. We report the case of a 60-year-old lady with cirrhosis, hypothyroidism, diabetes, hypertension, and history of methotrexate therapy for psoriasis presenting with decompensation of cirrhosis due to recurrent episodes of urinary tract infection. Urine microscopy showed the presence of S. larvae. The patient was treated with ivermectin after which her general condition improved.